Victimisation, Well‐being and Compensation: Using Panel Data to Estimate the Costs of Violent Crime. (20th July 2017) - Johnston, David W.; Shields, Michael A.; Suziedelyte, Agne
Abstract: The costs of violent crime victimisation are often left to a tribunal, judge or jury to determine, which can lead to considerable subjectivity and variation. Using panel data, this article provides compensation estimates that help reduce the subjectivity of awards by providing a benchmark for the compensation required to offset direct and intangible costs. Individual‐area fixed‐effects models of well‐being that allow for adaptation and the endogeneity of income suggest that, on average, A88, 000 is required to compensate a violent crime victim, with the amount being greater for females (A102, 000) than males (A79, 000).